Prosody meets pragmatics : A comparison of rhetorical questions, information-seeking questions, exclamatives, and assertions - Wochner, Daniela (My University, 2022)
This dissertation thesis is concerned with rhetorical questions in German at the prosody-meaning interface. The objective of this work was the elaboration of the theoretical background and the prosodic profile of rhetorical questions in comparison to information-seeking questions, exclamatives, and assertions. The theoretical part of the current thesis shows that rhetorical questions, like information-seeking questions, belong to the interrogative mode. That is, like information-seeking questions, they can occur with all sorts of syntactic form types and like information-seeking questions, they perform partitions of sets of propositions with one of the propositions being the true answer to a question. Lexical elements such as discourse particles and negative polarity items as well as certain morpho-syntactic structures enhance the rhetoricity of a question and facilitate its interpretation. The function of a rhetorical question, however, is detached from its grammatical make-up and the rhetorical meaning is added on a pragmatic level. Information-seeking questions are requests for answers and have the only purpose to gain information. The function of a rhetorical question in the discourse is to make a point, to express speaker belief. Therefore, regarding their function, rhetorical questions intersect with declarative assertions. Different to default assertions, however, rhetorical questions further convey the obviousness of their answer. Assertions that similarly to rhetorical questions convey obviousness are called strong assertions. The advantage of a rhetorical question over a strong assertion is that rhetorical questions are indirect speech acts and off-record strategies. The speaker cannot be pinned down to the rhetorical point of the question since she can always refer to its interrogative sentence structure and pass the question off as an information-seeking question. By using an exclamative, the speaker signals a violation of her assumed norm. Exclamatives are utterances that express surprise and astonishment. Regarding their syntactic structure, they intersect with interrogative and declarative sentences. Their classification has been a controversial subject in the linguistic literature. They may belong to the interrogative, declarative or even an exclamative mode. The current thesis regards them as belonging to the declarative mode. The exclamative function is added on a pragmatic level. The experimental part of the thesis explored the prosodic nature of rhetorical questions. The results of the current production data are in support of prior findings on the prosody of rhetorical questions. Furthermore, it shows that the prosodic features that have been found to distinguish rhetorical form information-seeking questions can also be found in exclamatives and strong assertions. This concerns the frequent occurrence of the (L+H)* accent, which within the framework of the current thesis is considered to be an emphatic accent, across all three utterance types. In this accent, both the low and high tone are aligned within the accented syllable, which distinguishes it from other rising accents that have either the low or the high tone aligned within the accented syllable. Moreover, rhetorical questions, exclamatives and strong assertions showed longer durations/ slower speaking rates, a lower pitch scaling in rising movements, differences in pitch range as well as a higher occurrence of initial breathy voice quality as compared to neutral information-seeking questions and assertions. While there is no direct (prosodic) form to (pragmatic) function mapping, some prosodic constructions appear to be preferred in certain utterance/ illocution types. For instance the high plateau contour (L+H)* H-% appears to be prototypical for rhetorical polar questions. Verb-first exclamatives and rhetorical wh- questions were often produced with (L+H)* L-% nuclear contours, and strong assertions with (L+!H)* L-% nuclear contours. However, a distinct rhetorical question prosody (or also an exclamative prosody) is implausible. Rather, speakers may choose to prosodically emphasize an utterance and adapt the prosodic characteristics in way they feel it appropriate in a given discourse. Ultimately, there appears no strict rule of how to express specific speaker attitudes or pragmatic functions by means of a distinct combination of prosodic features.
Keywords: Linguistik, Phonologie, Phonetik, Pragmatik; 400